Statistical modeling of premium pricing: the Malaysian motor insurance experience - Noriszura Ismail ,; Abdul Aziz Jemain, (Penerbit ukm, 2007)

(untitled)
This study proposes a statistical modeling for determining the price of motor insurance. The premium pricing, which is tailored to the regulation and economic environment of the Malaysian insurance industry, gives equal weights to both technical and practical elements. The technical element focuses on statistical modeling of claim frequency and claim cost, whereas the practical element centers on combining claims experience with both inflations and expenses